Dampak Edukasi PHBS terhadap Pencegahan ISPA pada Balita di Komunitas Pertanian - Paraswati, Mareta Deka; Kusuma, Erik; Kurnianto, Syaifuddin; Widianto, Eko Prasetya; Wibowo, Suhendra Agung; Suroso, Heri (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2025)
Background: Acute Respiratory Infection (ARI) remains a leading cause of morbidity among children under five, particularly in agrarian areas characterized by exposure to kitchen smoke, limited ventilation, and agricultural activities that potentially increase ARI risk. Community health cadres for under-five children, as the front line of community empowerment, often have limited knowledge regarding the relationship between household environment and ARI prevention. Aims: To assess the effect of Clean and Healthy Living Behavior (CHLB/PHBS) education on changes in the knowledge of child health cadres in preventing ARI among under-five children in agrarian areas. Methods: A pre-experimental study with a one-group pretest-posttest design was conducted to evaluate the impact of a 90-minute CHLB education session. The intervention combined interactive lectures, discussions, and visual media. Knowledge was measured using a validated 15-item questionnaire. Data were analyzed using the Wilcoxon Signed-Rank Test. Results: The mean knowledge score significantly increased from 6.20 ± 0.97 (pretest) to 12.97 ± 1.03 (posttest). Statistical analysis showed p = 0.000, indicating a significant difference. Before the intervention, 83.3% of cadres were in the low-knowledge category, whereas after the education, 90% achieved the high-knowledge category. Conclusion: CHLB education significantly improved the knowledge of child health cadres in preventing ARI among under-five children in agrarian areas. This approach proved to be effective and contextually relevant, with potential to serve as a model for cadre empowerment in ARI prevention.